Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Prestasi Hasil Belajar Bahasa Indonesia - Anam, Hairul; Wijaya, Herman (Lembaga Bale Literasi, 2023)
This study aimed to know the effect of the Problem Based Learning (PBL) method on the students achievement outcomes of Indonesian Language Learning at Class VIII MTs NW Aik Anyar Academic Year 2021/2022. The research used a quasi-experimental research design. The population of this study were all students of class VIII at MTs. NW Aik Anyar. Class VIII B was experimental class, while class VIII A is the control class. The research design used was Posttest-Only Control Group Design. Data collection techniques used tests. Analysis of the data used the analysis of the t-test Polled Variance. The results showed that the average value of the experimental class learning outcomes was 75,95 and the control class was 61,53. To test the normality of the experimental class data, X2count = 5,0605 with X2table = 11,070, because X2count < X2table, the data was normally distributed. And the normality test of the data for the control class produces X2count = 2,3486 with X2table = 11,070, because X2count< X2 table, the data was normally distributed. The results of the hypothesis test of learning outcomes show that t count > ttable is (3.383 > 1.684) which meant, H0 was rejected and Ha was accepted. So it could be concluded that